2004
DOI: 10.1128/ec.3.1.52-60.2004
|View full text |Cite
|
Sign up to set email alerts
|

C-Terminal Truncation of α-COP Affects Functioning of Secretory Organelles and Calcium Homeostasis in Hansenula polymorpha

Abstract: In eukaryotic cells, COPI vesicles retrieve resident proteins to the endoplasmic reticulum and mediate intra-Golgi transport. Here, we studied the Hansenula polymorpha homologue of the Saccharomyces cerevisiae RET1 gene, encoding ␣-COP, a subunit of the COPI protein complex. H. polymorpha ret1 mutants, which expressed truncated ␣-COP lacking more than 300 C-terminal amino acids, manifested an enhanced ability to secrete human urokinase-type plasminogen activator (uPA) and an inability to grow with a shortage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…To obtain the pKAM567A and pKAM567B plasmids (Figure 3), a linker obtained by annealing of the oligonucleotides 5′‐gatcc aagct tccca tggcg ccatg tcatg agtggc‐3′ and 5′‐gccact catga catgg cgcca tggga agctt ggatc‐3′ was introduced into the Pvu II site of the pKAM554 plasmid in two opposite orientations. The pKAM556 plasmid (Figure 3) was constructed by replacing the Kpn I– Pvu II fragment of pKAM555 with the HARS6 ‐bearing Kpn I– Eco RV fragment of the p2CHA6 plasmid (Chechenova et al , 2004). To obtain the pKAM558 plasmid, the HpLEU2 ‐containing Sal I– Bam HI fragment of the pCLHX plasmid (Sohn et al , 1996) was introduced between the Xho I and Bam HI sites of pKAM556.…”
Section: Methodsmentioning
confidence: 99%
“…To obtain the pKAM567A and pKAM567B plasmids (Figure 3), a linker obtained by annealing of the oligonucleotides 5′‐gatcc aagct tccca tggcg ccatg tcatg agtggc‐3′ and 5′‐gccact catga catgg cgcca tggga agctt ggatc‐3′ was introduced into the Pvu II site of the pKAM554 plasmid in two opposite orientations. The pKAM556 plasmid (Figure 3) was constructed by replacing the Kpn I– Pvu II fragment of pKAM555 with the HARS6 ‐bearing Kpn I– Eco RV fragment of the p2CHA6 plasmid (Chechenova et al , 2004). To obtain the pKAM558 plasmid, the HpLEU2 ‐containing Sal I– Bam HI fragment of the pCLHX plasmid (Sohn et al , 1996) was introduced between the Xho I and Bam HI sites of pKAM556.…”
Section: Methodsmentioning
confidence: 99%
“…However, the mechanisms of Ca 2+ delivery to the yeast ER are still unclear. The recent study of the Hansenula polymorpha ret1 mutant by the authors indicates that Ca 2+ can be transported to the ER via the COPI‐coated vesicles furnishing the Golgi‐to‐ER retrograde transport (Chechenova et al , 2004). Indeed, C‐terminal truncation of the α subunit of the COPI complex in H. polymorpha led to a sensitivity to Ca 2+ shortage and to a disturbance of the ER‐hosted processes, while the Golgi functions remained unaffected.…”
Section: Introductionmentioning
confidence: 99%
“…Since Pmr1p was first synthesized in ER, it could exert its function before it was transported to the Golgi apparatus (Dürr et al , 1998). Moreover, recent studies have indicated that Ca 2+ can be transported from the Golgi apparatus to the ER via the COPI‐coated vesicles furnishing the Golgi–ER retrograde transport (Chechenova et al , 2004).…”
Section: Discussionmentioning
confidence: 99%